A prospective study of foetomaternal outcome in placenta praevia - Kaul, Somika; Rami, Bijal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Placenta praevia is one of the serious obstetric problems with far reaching effects and a major cause of antepartum haemorrhage. The aim of the study was to evaluate the foetomaternal outcome of pregnancies with placenta praevia. Methods: The present study was a prospective case control study conducted in the Department of Obstetrics and Gynaecology, Lal Ded Hospital, Srinagar from August 2009 to October 2010. Results: Among the 100 cases of placenta praevia studied bleeding per vaginum was the most common presenting symptom. Major placenta praevia was more common (53%) than minor placenta praevia. 43% of the cases of placenta praevia delivered before 37 completed weeks as compared to only 6% in the control group. All cases of placenta praevia delivered by caesarean section. Maternal morbidity in terms of postpartum haemorrhage (32%), intraoperative bowel and bladder injury (2%) and intensive care unit admission (1%) was more in cases of placenta praevia. Foetal complications in terms of neonatal intensive care unit admission (19%), neonatal death (10%) and stillbirth (5%) were more in pregnancies with placenta praevia as compared to controls. 48% of patients with placenta praevia required transfusion of blood and blood products as compared to 4.5% among controls. Conclusions: There is a significant increase in maternal morbidity in pregnancies complicated with placenta praevia. Also, there is a higher incidence of foetal complications and neonatal death. Managing a case of placenta praevia is a challenge in present day obstetrics and it creates a huge burden on the health care system.